2005
DOI: 10.1152/ajpregu.00702.2004
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-induced increase in skeletal muscle vasodilatory responses in obese Zucker rats

Abstract: The purpose of this study was to test the hypothesis that exercise training improves microvascular function in obese Zucker rats, a model of obesity and type II diabetes. Animals were divided into four age-matched groups: lean sedentary (LS), lean exercise (LE), obese sedentary (OS), and obese exercise (OE). The exercise groups were treadmill-exercised from 5 to 11 wk of age, including a 2-wk acclimation period. Mean arterial pressure (MAP) was not significantly different between any of the groups. The OS had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 33 publications
8
76
0
Order By: Relevance
“…Furthermore, even in studies reporting an improvement in insulin sensitivity, there were no reductions in fasting plasma insulin concentrations (18,36,71). While our study involved 8 wk of exercise at 10 m/min, Xiang et al (74) exercised the rats for 4-5 wk at 24 m/min. However, the difference in intensity of exercise may not be responsible for the difference in the effect on insulin levels.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Furthermore, even in studies reporting an improvement in insulin sensitivity, there were no reductions in fasting plasma insulin concentrations (18,36,71). While our study involved 8 wk of exercise at 10 m/min, Xiang et al (74) exercised the rats for 4-5 wk at 24 m/min. However, the difference in intensity of exercise may not be responsible for the difference in the effect on insulin levels.…”
Section: Discussionmentioning
confidence: 66%
“…In a clinical trial involving children 8-14 yr of age, Reinehr et al (56) have reported that plasma leptin concentrations are a predictor of overweight reduction with a lifestyle intervention. Although we did not measure leptin levels, others (50,74) have reported that exercise does not reduce leptin levels in these rats.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, Xiang et al 19 showed that obese Zucker rats subjected to regular moderate exercise had lower IL-6 levels compared to obese sedentary rats. They also showed acetylcholineinduced vasodilatation was much more pronounced in the former group of rats.…”
Section: Il-6 and Tnf- Alterations With Exercise In Animal Modelsmentioning
confidence: 99%
“…Before the morphological changes take place [18,19,26,45,57], vasomotor dysfunction of microvessels may occur, which is considered to be one of the early alterations that occur in several cardiovascular diseases, as outlined by many recent reviews [9,11,12,29,32,44]. In humans with diabetes mellitus, impaired vasomotor function of the large conductance arteries is established [14].…”
Section: Changes In Vasomotor Function Of Coronary Arterioles In Typementioning
confidence: 99%